Speech Acts in Everyday Communication: A Case Study of Accounting Students at Politeknik Unggul LP3M - Sharina Amanda (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to describe the types of speech acts used in the everyday communication of students from the Accounting Department at Politeknik Unggul LP3M. A qualitative descriptive method was employed, utilizing documentation and participatory observation techniques on students' oral and written communication practices. The data, consisting of 80 utterances, were classified according to Searle’s five types of speech acts: representative, directive, expressive, commissive, and declarative. The results indicate that directive and representative speech acts are the most dominant, reflecting the function of communication as a means of sharing information and requesting assistance in academic settings. This study recommends strengthening students' pragmatic competence to enhance the effectiveness of academic and social communication.